The Use of Photos from Patch Test Reactions on Day 7 in Professional Ice Hockey Players in Sweden - Eriksson, Tomas; Isaksson, Marléne; Tegner, Yelverton; Engfeldt, Malin; Bruze, Magnus (International Journal of Occupational and Environmental Medicine, 2018)
Background A survey was undertaken in all ice hockey players in 26 professional teams in Sweden representing the 2 highest divisions. All players answered a questionnaire and the players from 6 teams, 3 from each one of the 2 divisions, were patch tested with 72 test preparations in a baseline series supplemented with a series representing the work environment of the players. For practical reasons, the patch testing and test reading on day 3 (D3) took place in the arenas of the teams. As a traditional dermatologist reading on D7 was impossible to perform in all but one team, the players and coaches were asked to use their mobile phones to take photos of the tested backs of the players on D7 and send to the investigative team. In one team a dermatologist reading took place on D7 independent of the mobile photos. Aim The aim of the study was to investigate if photos from mobile phones taken on D7 by the subjects themselves or someone helping them could add positive reactions to those noted from traditional test readings on D3. Materials and Methods 107 players in the 6 teams were patch tested and reading on D3 was performed in 103 of them. Mobile photos of the backs of 100 players were taken on D7. Results 5 photos obtained from the 100 players available for the second test reading on D7 had too bad quality to allow evaluation. Thus, photos of 95/103 (92.2%) players with a live dermatologist reading on D3 were evaluated. Besides 50 contact allergic reactions noted in 26 players on D3, 7 (14%) more positive reactions were registered in 5 players, in 2 without any reactions on D3. The 7 additional reactions were noted to 7 different sensitizers - oxidized linalool, mercapto mix, mercaptobenzothiazole, PFR-2 (resol resin based on phenol and formaldehyde), paraben mix, imidazolidinyl urea, and methylenedianiline. Conclusion 14% more contact allergic reactions were diagnosed when using photos of the tested backs of the players replacing the traditional dermatologist reading on D7.
Keywords: Allergic contact dermatitis; contact allergy; delayed hypersensitivity; mobile phone; tele-ermatology; validation.